Polyester elastomer resin composition
Patent Information
- Application Number
- JP2021554975
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-18
- Filing Date
- 2021-03-16
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-03-16
AI Technical Summary
【0015】 本発明のポリエステルエラストマー樹脂組成物は、ブロー成形工法においてパリソンを高速で射出した際の高せん断速度領域における溶融粘度を低減することで、メルトフラクチャーによるパリソン表面とシリンダー壁面との摩擦による樹脂流動の乱れを抑制し、表面の平滑性を向上させたブロー成形品を得ることができ、かつ溶融滞留時の熱安定性に優れ、パリソンのドローダウン、及び著しい粘度上昇が発生しない樹脂組成物である。
Smart Images

Figure 0007652076000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester elastomer resin composition. More specifically, the present invention relates to a resin composition that can provide a good appearance with few irregularities when a molten resin (parison) is injected at high speed from an accumulator in a blow molding process, and has excellent thermal stability when retained in a cylinder. [Background technology]
[0002] Generally, polyester elastomers produced by melt polycondensation have a relatively low melt viscosity, and therefore the melt tension of the parison extruded from the molding machine is insufficient, and the parison cannot withstand the drawdown of the parison itself or the air pressure when blow molding a hollow container, resulting in the problem that blow moldability cannot be ensured.
[0003] For this reason, a crosslinking agent such as an epoxy compound and a reaction catalyst such as an imidazole catalyst (tertiary amine) are blended with a polymer produced by the melt polycondensation method to increase the melt viscosity of the polyester elastomer to a level suitable for blow molding (Patent Document 1).
[0004] In addition, modifications have been made to polyester elastomers by blending them with crosslinking agents such as epoxy compounds and isocyanate compounds to increase the melt viscosity to a level suitable for blow molding and improve the impact resistance (Patent Document 2).
[0005] In addition to reactive compounds, it is also known that the addition of a small amount of sodium ionomer causes an interaction due to ionic crosslinking at the interface between the polyester elastomer matrix and the ionomer, thereby significantly improving the melt viscosity (Patent Document 3).
[0006] Furthermore, by blending a sodium type ionomer with a polyolefin resin having an epoxy group, the melt viscosity can be further improved significantly (Patent Document 4).
[0007] However, in the method described in Patent Document 1, although a melt viscosity suitable for blow molding is achieved, the reactivity between the carboxylic acid terminal of the polyester elastomer and the epoxy compound is insufficient, and a reaction occurs when the polyester elastomer remains in the molding machine, resulting in variations in melt viscosity and uneven thickness of the molded product.
[0008] In addition, the method described in Patent Document 2 does not provide sufficient melt viscosity for blow molding, and the drawdown and stretchability of the parison tend to decrease, so sufficient modification effects are not observed. Therefore, it is easily presumed that the range of conditions for blow molding is narrow, and the thickness deviation of the obtained hollow molded product becomes significant.
[0009] The method described in Patent Document 3 can increase the melt viscosity to a level suitable for blow molding without requiring a reactive compound, but the dispersibility of the ionomer changes during heat retention, and the Na ions contained in the ionomer exhibit nucleophilicity toward the molecular chains of the polyester elastomer, causing decomposition, resulting in an unstable melt viscosity.
[0010] In the method of Patent Document 4, although the melt viscosity is stable during heat retention, when the parison is ejected from the accumulator at high speed, the melt viscosity is too high in the high shear rate region, resulting in an uneven pattern caused by melt fracture on the surface of the parison, making it impossible to obtain a good appearance. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 11-323110 [Patent Document 2] Japanese Patent Application Publication No. 5-302022 [Patent Document 3] JP 2008-201866 A [Patent Document 4] Patent No. 4114118 Summary of the Invention [Problem to be solved by the invention]
[0012] An object of the present invention is to provide a polyester elastomer resin composition which, when a parison is injected from an accumulator at high speed in a blow molding process, can give a good appearance with little unevenness due to melt fracture, and which has excellent thermal stability when retained in a cylinder. [Means for solving the problem]
[0013] In order to achieve the above object, the present inventors have conducted extensive research and found that it is possible to obtain a polyester elastomer resin composition with excellent blow moldability by selecting and blending optimal epoxy compounds having two or more functionalities, epoxy group-containing polyolefin resins, and unmodified olefin elastomers, and have come to propose the present invention. That is, the present invention is as follows.
[0014] [1] A thermoplastic polyester elastomer (A) containing 0.1 to 5 parts by mass of a bifunctional or higher epoxy compound (B) having an epoxy value of more than 0.5 meq / g, 0.1 to 5 parts by mass of an epoxy group-containing polyolefin resin (C) having an epoxy value of 0.01 to 0.5 meq / g, and 0.1 to 15 parts by mass of an unmodified olefin elastomer (D), with a melt viscosity measured in accordance with JIS K7199 of 230°C at a shear rate of 6.08 sec -1 The melt viscosity is 6800 Pa·s or more at a shear rate of 6080 sec -1 The polyester elastomer resin composition has a melt viscosity of 160 Pa·s or less when heated to 50° C. [2] The polyester elastomer resin composition according to [1], wherein the hard segment of the thermoplastic polyester elastomer (A) is polybutylene terephthalate and the soft segment is an ethylene oxide addition polymer of poly(tetramethylene oxide) glycol and / or poly(propylene oxide) glycol. [3] The polyester elastomer resin composition according to [1] or [2], wherein the soft segment constituting the thermoplastic polyester elastomer (A) has a number average molecular weight of 500 to 4,000 and a copolymerization amount of 3 to 50 mol % based on the total glycol component. [4] The polyester elastomer resin composition according to any one of [1] to [3], wherein the unmodified olefin-based elastomer (D) is at least one selected from the group consisting of a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms, a copolymer of ethylene and styrene, and a copolymer of ethylene and an unsaturated compound other than an α-olefin. [5] The polyester elastomer resin composition according to any one of [1] to [4], wherein the unmodified olefin-based elastomer (D) has a melt flow rate of 0.1 to 15 g / 10 min at 190° C. under a load of 2.16 kg. [6] The polyester elastomer resin composition according to any one of [1] to [5], wherein the thermoplastic polyester elastomer (A) is copolymerized with an aromatic tricarboxylic acid in an amount of 0.01 to 3 mol % based on the total acid components.
[0015] The polyester elastomer resin composition of the present invention reduces the melt viscosity in the high shear rate region when a parison is injected at high speed in a blow molding process, thereby suppressing disturbance of the resin flow due to friction between the parison surface and the cylinder wall surface caused by melt fracture, and can produce a blow molded article with improved surface smoothness.The polyester elastomer resin composition of the present invention is also a resin composition that has excellent thermal stability during molten retention and does not cause drawdown of the parison or a significant increase in viscosity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] [Thermoplastic polyester elastomer (A)] The thermoplastic polyester elastomer (A) is composed of a hard segment and a soft segment. In general, the main components are a hard segment composed of a polyester composed of an aromatic dicarboxylic acid and an aliphatic or alicyclic diol, and at least one soft segment selected from an aliphatic polyether, an aliphatic polyester, and an aliphatic polycarbonate. In the present invention, the soft segment is preferably an aliphatic polyether. As the hard segment, the polyester composed of an aromatic dicarboxylic acid and an aliphatic or alicyclic diol is preferably 70% by mass or more, more preferably 80% by mass or more. As the soft segment, the aliphatic polyether is preferably 70% by mass or more, more preferably 80% by mass or more.
[0017] In the thermoplastic polyester elastomer (A) used in the present invention, the aromatic dicarboxylic acid constituting the polyester of the hard segment is not particularly limited, and is preferably terephthalic acid or 2,6-naphthalenedicarboxylic acid as the main aromatic dicarboxylic acid. Terephthalic acid or 2,6-naphthalenedicarboxylic acid is preferably 70 mol% or more of the total acid components, more preferably 80 mol% or more. Examples of other acid components include aromatic dicarboxylic acids such as diphenyldicarboxylic acid, isophthalic acid, trimellitic acid, trimesic acid, pyromellitic acid, and 5-sodium sulfoisophthalic acid, alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid and tetrahydrophthalic anhydride, and aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, dimer acid, and hydrogenated dimer acid. The other acid components are used in a range that does not significantly lower the melting point of the thermoplastic polyester elastomer, and the amount is preferably 30 mol% or less of the total acid components, more preferably 20 mol% or less.
[0018] The thermoplastic polyester elastomer (A) used in the present invention may contain aromatic tricarboxylic acid as an acid component in addition to aromatic dicarboxylic acid. By using aromatic tricarboxylic acid, the branching points in the molecular structure of the polyester elastomer are increased, and the relaxation time of the molecular chain under static standing due to entanglement is extended, and the melt viscosity is significantly improved in the low shear rate region. In this case, the relaxation time under flow is not significantly affected in the high shear rate region, so the melt viscosity can be maintained low.
[0019] The aromatic tricarboxylic acid used in the present invention is not particularly limited, but among them, trimellitic acid, trimesic acid, and hemimellitic acid, which can be purchased inexpensively on the market, are preferable. The copolymerization amount is preferably 0.01 to 3 mol% when the total acid components constituting the thermoplastic polyester elastomer (A) are taken as 100 mol%, more preferably 0.05 to 1 mol%, and even more preferably 0.08 to 0.5 mol%. If it is less than 0.01 mol%, the expected effect cannot be obtained, and if it exceeds 3 mol%, gelation occurs, and in batch polymerization, machine cleaning is required, and the yield during polymerization and continuous productivity decrease.
[0020] In the thermoplastic polyester elastomer (A) according to the present invention, the aliphatic or alicyclic diol constituting the polyester of the hard segment is generally aliphatic or alicyclic diol, and is not particularly limited, but is preferably an alkylene glycol having 2 to 8 carbon atoms. Specific examples include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, and 1,4-cyclohexanedimethanol. 1,4-butanediol and 1,4-cyclohexanedimethanol are most preferred.
[0021] As the component constituting the polyester of the hard segment, those composed of butylene terephthalate units (units composed of terephthalic acid and 1,4-butanediol) or butylene naphthalate units (units composed of 2,6-naphthalenedicarboxylic acid and 1,4-butanediol) are preferred in terms of physical properties, moldability, and cost performance. Those composed of butylene terephthalate units are particularly preferred.
[0022] In addition, the aromatic polyester suitable as the polyester constituting the hard segment in the thermoplastic polyester elastomer (A) according to the present invention can be easily obtained according to a normal polyester production method. In addition, when this polyester is used as a raw material for the thermoplastic polyester elastomer, such a polyester preferably has a number average molecular weight of 10,000 to 40,000.
[0023] Examples of the aliphatic polyether, which is a soft segment component in the thermoplastic polyester elastomer (A) used in the present invention, include poly(ethylene oxide) glycol, poly(propylene oxide) glycol, poly(tetramethylene oxide) glycol, poly(hexamethylene oxide) glycol, copolymers of ethylene oxide and propylene oxide, ethylene oxide addition polymers of poly(propylene oxide) glycol, and copolymers of ethylene oxide and tetrahydrofuran, and other poly(alkylene oxide) glycols. Among the poly(alkylene oxide) glycols, it is particularly preferable to use those having a side chain, a hydrocarbon structure with 3 or more carbon atoms, and steric hindrance, such as propylene oxide.
[0024] The reason why poly(alkylene oxide) glycols having steric hindrance and a hydrocarbon structure in the side chain are preferred is thought to be that, although the cause is not clear, when the molecular chains are entangled, fine entanglements occur, which lengthen the relaxation time, or interactions occur between the molecules, which dramatically improve the melt viscosity in the low shear rate region.
[0025] Among the above aliphatic polyethers, poly(tetramethylene oxide) glycol, ethylene oxide addition polymer of poly(propylene oxide) glycol, and copolymer glycol of ethylene oxide and tetrahydrofuran are preferred, and poly(tetramethylene oxide) glycol and ethylene oxide addition polymer of poly(propylene oxide) glycol are more preferred. The number average molecular weight of these soft segments in the copolymerized state is preferably about 500 to 4000.
[0026] If the number average molecular weight of the soft segment is less than 500, it may be difficult to exhibit elastomeric properties. On the other hand, if the number average molecular weight exceeds 4000, the compatibility with the polyester portion of the hard segment may decrease, making it difficult to copolymerize in blocks. The number average molecular weight of the soft segment is more preferably 800 to 3500, and even more preferably 1000 to 3500.
[0027] In the thermoplastic polyester elastomer (A), the copolymerization amount of the soft segment is preferably 3 to 50 mol % based on the total glycol components (the total of the aliphatic or alicyclic diol constituting the hard segment and the aliphatic polyether of the soft segment), more preferably 3 to 30 mol %, further preferably 3 to 20 mol %, and particularly preferably 3 to 15 mol %.
[0028] In the thermoplastic polyester elastomer (A) used in the present invention, the mass ratio of the hard segment to the soft segment (hard segment:soft segment) is generally preferably in the range of 30:70 to 95:5, more preferably 40:60 to 90:10, even more preferably 45:55 to 87:13, and particularly preferably 50:50 to 85:15.
[0029] The melting point of the thermoplastic polyester elastomer (A) is preferably 150 to 230° C., and more preferably 175 to 225° C. If the melting point of the thermoplastic polyester elastomer (A) is less than 150° C., the amount of soft segments is large and the heat resistance may decrease, whereas if it exceeds 230° C., the amount of hard segments is large and the flexibility may decrease.
[0030] The thermoplastic polyester elastomer (A) used in the present invention can be produced by known methods (e.g., JP-A-10-182954, WO 2007 / 072748, etc.). For example, any of the following methods may be used: a method of transesterifying a lower alcohol diester of a dicarboxylic acid, an excess amount of a low-molecular-weight glycol, and a soft segment component in the presence of a catalyst, and polycondensing the resulting reaction product; a method of esterifying a dicarboxylic acid, an excess amount of a glycol, and a soft segment component in the presence of a catalyst, and polycondensing the resulting reaction product; a method of randomizing a hard segment by transesterification by adding a soft segment component to the hard segment; a method of connecting a hard segment and a soft segment with a chain linking agent; and, when poly(ε-caprolactone) is used for the soft segment, an addition reaction of an ε-caprolactone monomer to the hard segment.
[0031] [Epoxy compound (B)] The epoxy compound (B) used in the present invention is a bifunctional or higher epoxy compound having an epoxy value of more than 0.5 meq / g. In other words, it is a compound having two or more epoxy groups, and is preferably one having good compatibility with the thermoplastic polyester elastomer (A). In order to thicken the resin composition to an extent that the blow moldability is satisfactory by reacting with the terminal group of the thermoplastic polyester elastomer (A), the epoxy compound (B) needs to have an epoxy value of more than 0.5 meq / g and contain two or more epoxy groups. The weight average molecular weight (Mw) of the epoxy compound (B) is preferably 100 or more, and the epoxy value is preferably 1.0 meq / g or more. The weight average molecular weight (Mw) of the epoxy compound (B) is more preferably 200 to 10,000, and even more preferably 200 to 1,000. The epoxy value of the epoxy compound (B) is more preferably 5.0 to 20 meq / g. When using a commercially available epoxy compound (B), the weight average molecular weight (Mw) is the value measured by the manufacturer. When epoxy compound (B) is a single compound, the weight average molecular weight is considered to be the molecular weight of that compound. When using a commercially available epoxy compound (B), the epoxy value is the value measured by the manufacturer. When the epoxy compound (B) is a single compound, the epoxy value can be calculated from its structure.
[0032] Specific examples of the epoxy compound (B) having two or more functional groups include 1,6-dihydroxynaphthalene diglycidyl ether, 1,3-bis(oxiranylmethoxy)benzene, 1,3,5-tris(2,3-epoxypropyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and diglycerol triglycidyl ether having three epoxy groups, and 1-chloro-2,3-epoxypropane-formaldehyde-2,7-naphthalene diol polycondensate and pentaerythritol polyglycidyl ether having four epoxy groups. Among them, polyfunctional epoxy compounds having heat resistance in the skeleton are preferable. In particular, bifunctional or tetrafunctional epoxy compounds having a naphthalene structure as a skeleton, or trifunctional epoxy compounds such as tris(2,3-epoxypropyl)isocyanurate having a triazine structure as a skeleton are preferable. Considering the degree of increase in the solution viscosity of the thermoplastic polyester elastomer (A), the effect of efficiently reducing the acid value of the thermoplastic polyester elastomer (A), and the degree of gelation caused by aggregation and solidification of the epoxy itself, a difunctional or trifunctional epoxy compound is preferred.
[0033] As the difunctional or higher functional epoxy compound (B), a polymer containing a glycidyl group can also be used, for example, a glycidyl group-containing styrene-based polymer.
[0034] The blending ratio (content ratio) of the thermoplastic polyester elastomer (A) and the epoxy compound (B) in the resin composition of the present invention is (A) / (B)=100 / 0.1-5 in mass ratio. If the epoxy compound (B) is more than 5 parts by mass, it may cause gelation due to reaction with the thermoplastic polyester elastomer. If the epoxy compound (B) is less than 0.1 parts by mass, the thickening effect is reduced, which is not preferable. The mass ratio (A) / (B) is preferably 100 / 0.1-3, more preferably 100 / 0.2-2. In the present invention, the blending amount (blending ratio) of each component is directly the content (content ratio) in the polyester elastomer resin composition.
[0035] When the difunctional or higher functional epoxy compound (B) is a single compound having a molecular weight of 200 to 1000, its mass ratio is preferably 0.1 to 0.33 parts by mass, and more preferably 0.2 to 0.32 parts by mass, per 100 parts by mass of the thermoplastic polyester elastomer (A).
[0036] [Epoxy group-containing polyolefin resin (C)] The epoxy group-containing polyolefin resin (C) used in the present invention is a polyolefin resin modified with epoxy, and has an epoxy value of 0.01 to 0.5 meq / g. The epoxy group-containing polyolefin resin (C), like the epoxy compound (B), reacts with the end group of the thermoplastic polyester elastomer (A) to thicken the resin composition to an extent that the blow moldability is satisfactory, and also plays the role of a compatibilizer that makes the thermoplastic polyester elastomer (A) and the unmodified olefin elastomer (D) compatible. In addition, the epoxy group-containing polyolefin resin (C) contributes to stabilizing the melt viscosity of the resin composition during melt retention due to its moderate epoxy value. The epoxy value of the epoxy group-containing polyolefin resin (C) is preferably 0.05 to 0.45 meq / g, more preferably 0.1 to 0.3 meq / g. If the epoxy value is less than 0.01 meq / g, the compatibility with the thermoplastic polyester elastomer (A) decreases, causing pulsation in the strand state before cutting. If the epoxy value exceeds 0.5 meq / g, the melt viscosity increases during heat retention, and the crosslinking points themselves gradually become coarse, causing gelation.
[0037] The epoxy group-containing polyolefin copolymer (C) is preferably a ternary copolymer consisting of an α-olefin, an unsaturated compound other than an α-olefin, and a glycidyl ester of an α,β-unsaturated acid. Examples of the α-olefin include ethylene, propylene, and 1-butene, with ethylene being preferred. Examples of the unsaturated compound other than the α-olefin include vinyl ethers, vinyl acetate, vinyl propionate, and other vinyl esters, acrylic acid and methacrylic acid methyl, ethyl, propyl, and butyl esters, acrylonitrile, and styrene, with butyl acrylate, methyl acrylate, and methyl methacrylate being preferred. Examples of the glycidyl ester of an α,β-unsaturated acid include acrylic acid glycidyl ester, methacrylic acid glycidyl ester, and ethacrylic acid glycidyl ester, with methacrylic acid glycidyl ester being preferred.
[0038] The amount of epoxy group-containing polyolefin resin (C) blended (content) is 0.1 to 5 parts by mass, preferably 0.3 to 4 parts by mass, more preferably 0.5 to 3 parts by mass, and further preferably 0.8 to 2.5 parts by mass, based on 100 parts by weight of thermoplastic polyester elastomer (A). If the blended amount is less than 0.1 part by mass, the resin does not exhibit the effect as a compatibilizer, whereas if it exceeds 5 parts by mass, the acid terminals of the thermoplastic polyester elastomer (A) react with the epoxy groups during retention, causing gelation.
[0039] [Unmodified olefin elastomer (D)] The unmodified olefin elastomer (D) (hereinafter, sometimes referred to as olefin elastomer (D)) is an olefin elastomer having no reactive groups such as epoxy groups, carbodiimide groups, oxazoline groups, and carboxyl groups. The olefin elastomer is preferably at least one selected from a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms, a copolymer of ethylene and styrene, and a copolymer of ethylene and an unsaturated compound other than an α-olefin. The present inventors have found, through extensive research, a mechanism in which, by blending an unmodified olefin elastomer (D), the melt viscosity is improved under static conditions such as low shear rate ranges, even if molecular chain extension is not performed, due to tension at the interface between the matrix thermoplastic polyester elastomer (A) and the olefin elastomer (D), and further, the melt viscosity is reduced under flow conditions such as high shear rate ranges.
[0040] The copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms used in the present invention is a copolymer containing as constituent components ethylene and at least one α-olefin having 3 to 20 carbon atoms. Specific examples of the α-olefin having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, and 3-methyl-1-butene. , 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and combinations thereof. Among these α-olefins, copolymers using α-olefins having 3 to 12 carbon atoms are preferred.
[0041] The copolymer of ethylene and styrene used in the present invention is not particularly limited, but hydrogenated one is preferable. For example, hydrogenated styrene-conjugated diene block copolymer can be mentioned. Styrene-conjugated diene block copolymer is a block copolymer consisting of a styrene block and a diene block, and includes diblock copolymer, triblock copolymer, radial block copolymer, etc. In addition, diene block components include butadiene block and isoprene block. Specific examples of hydrogenated styrene-diene block copolymer include styrene-ethylene-butylene-styrene block copolymer (SEBS) which is a hydrogenated product of styrene-butadiene-styrene block copolymer (SBS), styrene-ethylene-propylene-styrene block copolymer (SEPS) which is a hydrogenated product of styrene-isoprene-styrene block copolymer (SIS), and styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS) which is a hydrogenated product of styrene-butadiene / isoprene-styrene block copolymer (SBIS). As explained above, the copolymer of ethylene and styrene does not necessarily need to use ethylene as a raw material monomer, and it is sufficient that the copolymer obtained is equivalent to a copolymer obtained using ethylene as a raw material.
[0042] The copolymer of ethylene and an unsaturated compound other than an α-olefin used in the present invention is not particularly limited. Examples of the unsaturated compound other than an α-olefin include vinyl ethers, vinyl esters such as vinyl acetate and vinyl propionate, methyl, ethyl, propyl, butyl and other esters of acrylic acid and methacrylic acid, acrylonitrile and styrene, and among these, butyl acrylate, methyl acrylate, and methyl methacrylate are preferred.
[0043] The olefin elastomer (D) used in the present invention preferably has a melt flow rate of 0.1 to 15 g / 10 min at 190° C. under a load of 2.16 kg. More preferably, it is 2 to 10 g / min. If the melt flow rate exceeds 15 g / min, the compatibility with the thermoplastic polyester elastomer (A) of the matrix decreases, and the strand starts to pulsate.
[0044] The blending (content) amount of the unmodified olefin-based elastomer (D) is 0.1 to 15 parts by mass, preferably 1 to 12 parts by mass, more preferably 2 to 10 parts by mass, and further preferably 3 to 9 parts by mass, based on 100 parts by weight of the thermoplastic polyester elastomer (A). If the blending amount is less than 0.1 part by mass, the polyester elastomer resin composition may have a shear rate of 6.08 sec -1 If the amount of the unmodified olefin elastomer (D) exceeds 15 parts by mass, the unmodified olefin elastomer (D) will not be compatible with the thermoplastic polyester elastomer (A) and will separate from the thermoplastic polyester elastomer (A), resulting in poor appearance and unstable melt viscosity behavior during retention.
[0045] Furthermore, the polyester elastomer resin composition of the present invention can be blended with various additives according to the purpose within a range that does not impair the effects of the present invention. As additives, known light stabilizers such as phenols, sulfurs, phosphorus, hindered amines, triazoles, benzophenones, benzoates, nickel, and salicylic acids, antistatic agents, lubricants, molecular regulators such as peroxides, metal deactivators, organic and inorganic nucleating agents, neutralizing agents, antacids, antibacterial agents, fluorescent brighteners, fillers, flame retardants, flame retardant assistants, organic and inorganic pigments, etc., can be added. The polyester elastomer resin composition of the present invention preferably contains 80% by mass or more of the thermoplastic polyester elastomer (A), the bifunctional or higher epoxy compound (B), the epoxy group-containing polyolefin resin (C), and the unmodified olefin elastomer (D) in total, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0046] The polyester elastomer resin composition of the present invention has the above-mentioned constitution, and has a melt viscosity measured in accordance with JIS K7199 at 230°C and a shear rate of 6.08 sec -1 The melt viscosity is 6800 Pa·s or more at a shear rate of 6080 sec -1 The melt viscosity at shear rate is 160 Pa·s or less. -1 The melt viscosity at shear rate of 6080 sec is preferably 7000 Pa·s or more, and more preferably 7200 Pa·s or more. -1 The melt viscosity at shear rate of 6.08 sec is preferably 158 Pa·s or less, more preferably 156 Pa·s or less. -1 The upper limit of the melt viscosity at shear rate is not particularly limited, but is preferably 9000 Pa·s or less. -1 The lower limit of the melt viscosity at this time is not particularly limited, but is preferably 100 Pa·s or more.
[0047] The polyester elastomer resin composition of the present invention preferably has a melt flow rate after retention at 240° C. for 6 minutes under a load of 5.0 kg, and a melt flow rate after retention at 240° C. for 26 minutes change of ±1.0 g / 10 min. The polyester elastomer resin composition preferably has a melt flow rate after retention at 240° C. for 6 minutes under a load of 5.0 kg of 2.0 to 5.5 g / 10 min, more preferably 2.5 to 5.0 g / 10 min.
[0048] The polyester elastomer resin composition of the present invention preferably has a surface hardness of an injection molded or blow molded article made from the composition falling within a range of Shore D hardness of 40 to 65. The surface hardness is more preferably 45 to 60 on a Shore D hardness basis.
[0049] The polyester elastomer resin composition of the present invention can be produced by melt-kneading the resin using a conventional thermoplastic resin mixer, typically a single-screw or twin-screw melt-kneader or a kneader-type heater, followed by pelletizing the mixture in a granulation step. EXAMPLES
[0050] In order to explain the present invention in more detail, examples are given below, but the present invention is not limited to these examples. The measured values described in the examples were measured by the following methods.
[0051] Melting point: Using a differential scanning calorimeter "DSC220" manufactured by Seiko Electronics Co., Ltd., 5 mg of the measurement sample was placed in an aluminum pan, the lid was pressed down to seal it, and the sample was held at 250°C for 5 minutes to completely melt the sample, then quenched with liquid nitrogen, and then measured at a heating rate of 20°C / min from -150°C to 250°C. The endothermic peak of the obtained thermogram curve was taken as the melting point.
[0052] Reduced Viscosity: 0.10 g of the thoroughly dried resin was dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4), and the viscosity was measured at 30° C. using an Ubbelohse viscometer.
[0053] Acid Number: 0.2 g of the sample was precisely weighed and dissolved in 20 ml of chloroform, and the content was determined by titration with 0.01 N potassium hydroxide (ethanol solution). Phenolphthalein was used as the indicator.
[0054] The following raw materials were used: [Thermoplastic polyester elastomer (A)] Polyester elastomer A1 According to the method described in Reference Example 1 of paragraph 0017 of JP-A-9-59491, a polyester elastomer having a molar ratio of terephthalic acid / 1,4-butanediol / poly(tetramethylene oxide) glycol (PTMG; number average molecular weight 1000) of 100 / 88 / 12 was produced. This polyester elastomer A1 had a melting point of 200° C., a reduced viscosity of 1.86 dl / g, and an acid value of 45 eq / t. Polyester elastomer A2 According to the method described in Reference Example 1 of paragraph 0017 of JP-A-9-59491, a polyester elastomer having an ethylene oxide addition polymer of terephthalic acid / 1,4-butanediol / poly(propylene oxide) glycol (PPG-PEG; number average molecular weight 3100, propylene oxide / ethylene oxide 60 / 40 (molar ratio)) of 100 / 96.2 / 3.8 (molar ratio) was produced. This polyester elastomer A2 had a melting point of 218° C., a reduced viscosity of 1.40 dl / g, and an acid value of 33 eq / t. Polyester elastomer A3 According to the method described in Reference Example 1 of paragraph 0017 of JP-A-9-59491, a polyester elastomer having an ethylene oxide addition polymer of terephthalic acid / trimellitic acid / 1,4-butanediol / poly(propylene oxide) glycol (PPG-PEG; number average molecular weight 3100, propylene oxide / ethylene oxide 60 / 40 (molar ratio)) of 99.9 / 0.1 / 96.2 / 3.8 (molar ratio) was produced. This polyester elastomer A3 had a melting point of 217° C., a reduced viscosity of 1.38 dl / g, and an acid value of 35 eq / t.
[0055] [Epoxy group-containing compound (B)] B-1 (TEPIC-S) N-substituted triisocyanurate (tris(2,3-epoxypropyl)isocyanurate) TEPIC-S (Nissan Chemical Industries, Ltd., molecular weight 297, epoxy value 10.1 meq / g) B-2 (UG-4070) Glycidyl group-containing styrene acrylic polymer ARUFON UG-4070 (manufactured by Toa Gosei Co., Ltd., Mw: 9700, epoxy value 1.4 meq / g)
[0056] [Epoxy group-containing polyolefin resin (C)] C-1 (BF-7L) Epoxy group-containing olefin copolymer: Bondfast BF-7L, manufactured by Sumitomo Chemical Co., Ltd., epoxy value: 0.2 meq / g C-2 (BF-7M) Epoxy group-containing olefin copolymer: Bondfast BF-7M, manufactured by Sumitomo Chemical Co., Ltd., epoxy value: 0.4 meq / g C-3 (AX8900) [An epoxy group-containing polyolefin resin for comparison.] Epoxy group-containing olefin copolymer: Rotader AX8900, manufactured by Arkema, epoxy value: 0.6 meq / g
[0057] [Unmodified olefin elastomer (D)] D-1(29MA03T) Ethylene-methyl methacrylate copolymer: Lotril 29MA03T, manufactured by Arkema, ethylene / methyl methacrylate ratio = 71 / 29 (mass ratio), MFR (190 °C, 2.16 kg) = 3.0 g / 10 min D-2(H1221) Styrene-ethylene-butylene-styrene block copolymer: Tuftec H1221, Asahi Kasei Corporation, styrene / ethylene-butylene ratio = 12 / 88 (mass ratio), MFR (190°C, 2.16 kg) = 4.5 g / 10 min D-3(A-4050S) Ethylene-butene copolymer: TAFMER A-4050S, manufactured by Mitsui Chemicals, ethylene / butene ratio = 80 / 20 (mass ratio), MFR (190°C, 2.16 kg) = 6.5 g / 10 min D-4(35BA40T) Ethylene / methyl methacrylate copolymer: Lotryl 35BA40T, manufactured by Arkema, ethylene / methyl methacrylate ratio = 65 / 35 (mass ratio), MFR (190 °C, 2.16 kg) = 35 g / 10 min D-5 (M1943) [An olefin-based elastomer for comparison.] Styrene-ethylene-butylene-styrene block copolymer: Tuftec M1943, manufactured by Asahi Kasei Corporation, styrene / ethylene-butylene ratio = 20 / 80 (mass ratio), MFR (190°C, 2.16 kg) = 8.0 g / 10 min, modified with maleic acid, acid value = 10 eq / t
[0058] [Other additives] Release agent: Licowax E, Clariant Antioxidant: Irganox 1010, manufactured by BASF
[0059] Examples 1 to 8, Comparative Examples 1 to 10 The above components were dry blended in the ratios shown in Table 1, and kneaded and pelletized in a twin-screw extruder. The pellets of the polyester elastomer resin composition were used to carry out the following evaluations. The results are shown in Table 1.
[0060] Compatibility: The strand state before pelletization was visually inspected. ○: The strand is drawn without any problems, and no coarse resin is generated near the die. △: The strands pulsate slightly. ×: The strand pulsates and coarse resin is generated near the die.
[0061] Surface hardness: The surface hardness was measured in an environment of 23°C according to the test method (Shore D) described in ASTM D2240. The test pieces were injection molded at a cylinder temperature of 240°C, and three 100mm x 100mm x 2mm (thickness) square test pieces were stacked on top of each other, and the instantaneous value of Shore D when a needle tip was dropped on them was read to measure the surface hardness.
[0062] Melt Viscosity: According to JIS K7199, a capillary rheometer (Toyo Seiki F-1) was used to measure the shear rate at 0.5 mm / min (6.08 sec -1 ) to 500mm / min (6080sec -1 The melt viscosity was measured when the shear rate was changed to 6.08 sec at a measurement temperature of 230°C. -1 Melt viscosity at shear rate of 60 to 80 sec -1 The melt viscosity was measured at this time. The nozzle shape was a capillary diameter of 1.0 mm and a capillary length of 10 mm.
[0063] Melt Flow Rate: According to the test method (Method A) described in JIS K7210, the melt flow rate (MFR: g / 10 min) was measured at a measurement temperature of 240° C., a load of 5000 g, and a residence time of 6 minutes and 26 minutes. A composition with a moisture content of 0.1 mass% or less was used for the measurement.
[0064] [Evaluation of blow molding] The cylinder temperature of the direct blow molding machine (single screw extruder: L / D=25, full flight screw, screw diameter 65mm) was set to 180-240℃ to manufacture the direct blow molded products. A die lip for forming a parison was attached to the tip of the cylinder, and equipment was required that could seal the blow air inside the mold. The speed at which the parison was ejected from the accumulator was adjusted by adjusting the air valve, with a shear rate of 60-80 sec -1 The inner and outer surfaces of the molded product were observed to confirm whether a molded product with good surface smoothness had been obtained. ○: No surface irregularities due to melt fracture, and smoothness is good ×: Surface unevenness is severe due to melt fracture -: Not rated
[0065] [Retention stability] Using the above-mentioned blow molding machine, a molten resin composition was retained in the cylinder, the screw was rotated, and a purging state was established, and confirmation was carried out from the viewpoint of shape retention and drawdown of the parison. ○: No drawdown of the parison or significant increase in viscosity occurs after retention ×: Drawdown of the parison and / or a significant increase in viscosity was observed after retention -: Not rated
[0066] [Table 1]
[0067] Examples 1 to 8 are resin compositions in which a thermoplastic polyester elastomer (A) is mixed with an epoxy compound (B), an epoxy group-containing polyolefin resin (C), and an unmodified olefin-based elastomer (D) as specified, and the resin compositions have excellent direct blow moldability during high-speed injection and excellent retention stability in a cylinder. In addition, the hardness of the molded product obtained has a desirable elastic modulus. Furthermore, in Examples 1 to 6 and 8, the component (D) having a specific MFR is used compared to Example 7, so the compatibility of the resin composition is good and there is no pulsation of the strand during production.
[0068] In Comparative Example 1, only the epoxy compound (B) was blended, and the melt viscosity in the low shear rate region was insufficient, causing drawdown during retention. In Comparative Example 2, only the epoxy compound (B) was blended. The melt viscosity was high in the low shear rate region but high in the high shear rate region, causing melt fracture during blow molding and failing to provide a good appearance. Comparative Example 3 has excellent melt viscosity in the low shear rate and high shear rate regions, but since the epoxy group-containing polyolefin resin (C) is not added, the melt viscosity cannot be maintained during retention, and the product lacks robustness in terms of thickness stability. In Comparative Example 4, since the unmodified olefin-based elastomer (D) is not added as in the prior art, the melt viscosity in the low shear rate region is low. Comparative Example 5 has excellent melt viscosity in the low shear rate and high shear rate regions, but since the epoxy group-containing polyolefin resin (C) is not added, the melt viscosity cannot be maintained during retention, and the product lacks robustness in terms of thickness stability. In Comparative Example 6, since an epoxy group-containing polyolefin resin with a high epoxy value was added, the melt viscosity improved in the low shear rate region, but the melt viscosity increased in the high shear rate region, resulting in a lack of inner surface smoothness during blow molding. In Comparative Example 7, the amount of epoxy group-containing polyolefin resin (C) added was too large, so that the melt viscosity increased in the high shear rate region, and the inner surface smoothness during blow molding was lacking. In Comparative Example 8, the amount of unmodified olefin-based elastomer (D) added was too large, so that the molded article produced by injection molding had a hardness that was too soft and was not optimal for an actual molded article. In Comparative Example 9, a maleic acid-modified olefin elastomer was added, which reacted with the epoxy compound or the epoxy group-containing polyolefin resin, increasing the melt viscosity in the low shear rate region and the high shear rate region, resulting in a lack of inner surface smoothness during blow molding. In Comparative Example 10, the epoxy group-containing polyolefin resin (C) reacted too much with the polyester elastomer (A) and the compatibility progressed too much, so that the effect of adding the unmodified olefin elastomer (D) was not obtained. [Industrial Applicability]
[0069] In the present invention, it is possible to obtain a blow molded article having excellent surface smoothness with few irregularities on the inner and outer surfaces, and to obtain a molded article having excellent robustness against variations in wall thickness. As a result, it is possible to manufacture an intake pipe with little pressure loss and good fuel efficiency for use in an automobile intake pipe equipped with a turbocharger system. In addition, it is useful for other automobile parts applications, home appliance parts applications, etc. that require the above-mentioned excellent properties.
Claims
1. The composition contains, relative to 100 parts by mass of a thermoplastic polyester elastomer (A), 0.1 to 5 parts by mass of a bifunctional or higher functional epoxy compound (B) having an epoxy value of more than 0.5 meq / g, 0.1 to 5 parts by mass of an epoxy group-containing polyolefin resin (C) having an epoxy value of 0.01 to 0.5 meq / g, and 0.1 to 15 parts by mass of an unmodified olefin elastomer (D), The thermoplastic polyester elastomer (A) has a hard segment that is polybutylene terephthalate and a soft segment that is an ethylene oxide addition polymer of poly(tetramethylene oxide) glycol and / or poly(propylene oxide) glycol, the number average molecular weight of the soft segment constituting the thermoplastic polyester elastomer (A) is 500 to 4,000, and the copolymerization amount is 3 to 50 mol % based on the total glycol component; The melt viscosity measured according to JIS K7199 was 230°C at a shear rate of 6.08 sec. -1 The melt viscosity at this time is 6800 Pa·s or more, and the shear rate is 6080 sec -1 The polyester elastomer resin composition has a melt viscosity of 160 Pa·s or less when heated to 50° C.
2. The polyester elastomer resin composition according to claim 1, wherein the unmodified olefin-based elastomer (D) is at least one selected from the group consisting of a copolymer of ethylene and an α-olefin having 3 to 20 carbon atoms, a copolymer of ethylene and styrene, and a copolymer of ethylene and an unsaturated compound other than an α-olefin.
3. 3. The polyester elastomer resin composition according to claim 1, wherein the unmodified olefin-based elastomer (D) has a melt flow rate of 0.1 to 15 g / 10 min at 190° C. under a load of 2.16 kg.
4. 4. The polyester elastomer resin composition according to claim 1, wherein the thermoplastic polyester elastomer (A) is copolymerized with an aromatic tricarboxylic acid in an amount of 0.01 to 3 mol % based on the total acid components.
Citation Information
Patent Citations
Polyester polyester block copolymer composition
JP1993302022A
Polyester elastomer resin composition
JP1999323110A
Polyester elastomer resin and resin composition
JP2001002768A
Polyester-based elastomer foam, and sealing material constituted by the same and used for electric / electronic instrument
JP2008045120A
Polyester elastomer-based resin composition excellent in expansion-molding property
JP2008201866A